Beyond Financial Numbers: The Role of Green Accounting, ESG Disclosure, and Digital Transparency in Enhancing Firm Value within the Sustainability Economy - Muhammad Hafis Akbar Nasution; Andreasta Ginting; Emi Uliyanty Br Sidabutar (Manunggal Halim Jaya, 2026)
This study examines the role of green accounting, Environmental, Social, and Governance (ESG) disclosure, and digital transparency in enhancing firm value within the sustainability economy. The research aims to move beyond traditional financial perspectives by exploring how sustainability-oriented accounting and reporting practices contribute to corporate value creation. Adopting a qualitative research approach grounded in a comprehensive literature review, this research systematically analyzes and synthesizes prior empirical and theoretical studies published in reputable international journals. The method emphasizes qualitative content analysis to identify dominant themes, patterns, and conceptual linkages among green accounting practices, ESG disclosure mechanisms, digital transparency, and firm value. The findings reveal that green accounting enables firms to internalize environmental impacts and strengthen long-term performance legitimacy. At the same time, ESG disclosure functions as a strategic signaling mechanism that reduces information asymmetry and enhances stakeholder trust. Furthermore, digital transparency is found to amplify the value relevance of sustainability disclosures by improving the accessibility, timeliness, and credibility of non-financial information. The study also identifies that the effectiveness of these practices is highly context-dependent, influenced by institutional environments, reporting quality, and digital maturity. Overall, the study concludes that integrating green accounting, ESG disclosure, and digital transparency is essential for firms seeking to enhance sustainable firm value beyond financial numbers. These findings provide important theoretical insights and managerial implications for advancing sustainability-oriented corporate reporting.